An empirical analysis of the determinant of bank asset risks in Southeast Asia - Sumprasert, Sukhita (2018)
Since the single market has come into the centre of debate for Southeast Asian economic growth, it provides opportunities for strong banks to expand internationally while signals local banks to strengthen their competitiveness. Otherwise, underperformed banks may face the situations of merger and acquisition from foreign banks or have to leave the market. Thus, the need for performance evaluation of banks in the region scale should be taking place to ensure bank financial soundness and identify key driver indicators for bank profitability. In fact, many available literatures have been conducting in the context of bank profitability determinant analysis, but less of them are placing on Southeast Asia bank data. Moreover, there are even less studies apply a comprehensive view to select the factors into the analysis. To fulfill the literature gaps, this dissertation aims to empirically analyse the determinants of bank profitability that is measured by net interest margin (NIM) of Southeast Asian banks and adopted the CAMELS framework to explore variety of the determinants from six key components. The bank dataset is scoped on six leading countries in Southeast Asia such as Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam during 2008 to 2017. The unbalance panel data is analysed by using multivariate regression model with pooled OLS technique to develop two model with different combination of regressors. The empirical results of the two model show high predictive power around 90% and no presence of multicollinearity issue in which this could be a benefit from applying CAMELS framework as a variable selection guideline. In addition, the two models give consistent findings in that bank net interest margin can be mostly explained by the indicators from three main categories such as asset quality, management efficiency and earning capacity. Moreover, the study examines the effect from banking services and found Islamic services seem not be an influencer to net interest margin, whereas investment service effect positively. In the light of the empirical evidence, the implications for bank policies should consider for the reduction in average operating cost as well as maximise resource to improve efficiency levels. Meanwhile, economic policy should be implemented to create an environment of low credit risk and concern for reducing interest margins. This would encourage banks in preparing themselves to be strongly compete with international banks that are fully equipped with superior knowledge and financial techniques and also would, in turn, make the financial intermediation less costly to the society.